2002
DOI: 10.1063/1.1530747
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced decomposition of single-wall carbon nanotubes adsorbed on H/Si(111)

Abstract: The thermally driven reaction of carbon nanotubes with a silicon substrate is studied by photoemission spectroscopy and atomic force microscopy. Carbon nanotubes with a relatively high defect density are observed to decompose under reaction with silicon to form silicon carbide at temperatures ͑650Ϯ10°C͒ substantially lower than the analogous reaction for adsorbed C 60 . The morphology of the resultant silicon carbide islands appears to reflect the morphology of the original nanotubes, suggesting a means by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, a variation of this method, in which SWNTs are deposited from a liquid suspension onto a fine W mesh, has been used elsewhere. , Method b is a workable solution; however, many reagents of interest will chemisorb readily at room temperature on Si, Ge, and their oxides as well as on SWNTs which complicates the interpretation of spectroscopic data. There is also the potential problem of reaction (e.g., SiC formation) during cleaning of the SWNTs by annealing in ultrahigh vacuum (UHV).…”
Section: Introductionmentioning
confidence: 99%
“…However, a variation of this method, in which SWNTs are deposited from a liquid suspension onto a fine W mesh, has been used elsewhere. , Method b is a workable solution; however, many reagents of interest will chemisorb readily at room temperature on Si, Ge, and their oxides as well as on SWNTs which complicates the interpretation of spectroscopic data. There is also the potential problem of reaction (e.g., SiC formation) during cleaning of the SWNTs by annealing in ultrahigh vacuum (UHV).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CNTs are chemically inert in the range of soldering temperatures. The oxidation and decomposition temperatures of CNTs were reported to be 530°C and 650°C, respectively [24,25]. Therefore, CNT can be adopted as a reinforcing material of most commercially available solders.…”
Section: Introductionmentioning
confidence: 99%
“…[152] and Hunt et al [153] reported in their studies that the decomposition temperature is being reduced for high contents of amorphous carbon due to the thermal oxidative stability of the nanotubes. MWCNTs-S3 displays the higher decomposition temperature and the lowest weight percent of amorphous carbon which confirms the lower defect sites along the sidewalls of the nanotubes.…”
Section: Raman Spectroscopy Was Performed On a Renishaw Invia Ramanmentioning
confidence: 99%